Analisis Rasio Kinerja Keuangan Bank Muamalat Indonesia Pada Masa Pandemi Covid-19 - Indah Harum Rezeki Rezeki; Heni Noviarita Noviarita (Faculty of Economics and Management, 2021)
This study was conducted to determine the financial performance of Bank Muamalat Indonesia in terms of financial ratios that were reported periodically during the Covid19 pandemic. This type of research is a descriptive study with a qualitative approach. The data collection technique used is through the documentation method, namely secondary data collection in the form of quarterly financial reports that have been published on the Bank Muamalat Indonesia website in 2020. The analysis technique used is a descriptive analysis by analyzing banking financial performance ratio data. The results of this study state that the financial performance of Bank Muamalat Indonesia during the Covid 19 the year 2020 pandemic was in a healthy condition from the aspects of capital, quality of earning assets, and liabilities. This is evidenced by the results of the value of the Capital Adequacy Ratio (CAR), Non-Performing Financing (NPF), and Financing to Debt Ratio (FDR) which are always at the standard value of a healthy bank financial performance. Meanwhile, in terms of profitability and operational management, Bank Muamalat Indonesia is in an unsanitary condition. This can be seen from the results of the ratio of Return on Assets (ROA), Operational Costs, and Operating Income (BOPO) which are always at ratios that do not comply with sound financial value standards.